Reduksi Limbah Kertas dan Kardus di Kabupaten Karawang Menjadi Eko Briket Melalui Usulan Perancangan Mesin Skala Produksi - Yamandito Mario Nugroho; Aksyal Abi Maulana; Gading Adithia Famella; Wahyu Fitrianto (Fakultas Teknik Universitas Tulang Bawang, 2026)
The problem of increasing waste generation in Indonesia, particularly in Karawang Regency, poses a serious environmental threat if not properly managed. One sustainable alternative is to utilize paper and cardboard waste as raw materials for eco-briquettes. This study aims to develop eco-briquette products and design a production machine capable of improving the efficiency of non-hazardous waste processing. The research method applied was experimental and engineering design. The experiment was conducted by producing several briquette samples with different compositions of paper, cardboard, and tapioca starch, which were then tested through burn duration and physical performance evaluation. The results showed that briquettes with a composition of 80% cardboard and 20% tapioca starch performed best, with a burn time of 21 minutes. Furthermore, a production system design was proposed, consisting of cutting, mixing, pressing, crushing, second mixing, and molding machines, with a production target of 100 briquettes per day. This design is projected to reduce paper and cardboard waste by approximately 1.197 tons per month. Therefore, this study demonstrates that utilizing non-hazardous waste for eco-briquette production not only provides a solution for waste reduction but also supports economic value and environmental sustainability. Keywords: Briquette, Design, Experiment, Paper, Waste